1972
DOI: 10.1136/gut.13.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of intestinal tuberculosis and its distinction from Crohn's disease

Abstract: SUMMARY Intestinal lesions of 212 cases presenting with symptoms of intestinal obstruction were studied. Of these, 159 cases were diagnosed as tuberculosis and 10 as Crohn's disease. Forty-three cases could not be classified into any of these entities and are excluded from this account. The amount of chemotherapeutic diugs received by each patient preoperatively was recorded. Cases proved as tuberculosis at the first operation were put on antituberculosis chemotherapy. Thirteen of these cases were operated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
163
0
7

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(177 citation statements)
references
References 29 publications
7
163
0
7
Order By: Relevance
“…Culture of acid‐fast bacilli (AFB) is the gold standard for a positive diagnosis of ITB 7, 8, 9. However, a positive yield of Mycobacterium tuberculosis (MTB) complex is obtained in only 25–50% of cases on culture of intestinal biopsy tissue,4, 7, 8, 9 making it difficult to test for drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Culture of acid‐fast bacilli (AFB) is the gold standard for a positive diagnosis of ITB 7, 8, 9. However, a positive yield of Mycobacterium tuberculosis (MTB) complex is obtained in only 25–50% of cases on culture of intestinal biopsy tissue,4, 7, 8, 9 making it difficult to test for drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Muhammad Saleem Shaikh SM Sisodia , Tandon HD, Anil Kumar, Veerabhadrarao Rao , reported that the majority of the patients were of age group between 20-40 yrs. [5][6][7][8][9] We observed that there is slight male preponderance with Male:Female ratio of 1.4:1, in the study conducted by Chalya PL. Male:female ratio was (1.4:1), in study by Urabinohatti KA ratio was 1.8:1, Awasthi S also reported ratio of 1.4:1, and male preponderance was the finding in most of the studies.…”
Section: Discussionmentioning
confidence: 84%
“…In 4 cases where there was no caseating granuloma in the resected sample, the diagnosis was based on both macro scopic and histologic findings of the resected samples, such as the presence of noncaseating granulomas with confluent tendency and the lack of fissuring and edema microscopically as well as the presence of transverse ulcerations with scarring macroscopically, as described by Tandon and Prakash (1972). In another 16 cases, which were treated non-surgically, the diagnosis was made on the basis of both the demonstration of noncaseating granulomas in biopsied tissue and therapeutic differential diagnosis with anti-tubercular therapy, in addition to the clinical features, x-ray findings and endoscopic findings.…”
Section: Methodsmentioning
confidence: 99%